A Pilot 6-Week Lifestyle Intervention in Women Aged 50+ in Ireland. Issue 1 (16th September 2022) - Cooper, Diane; Kavanagh, Ruth; Bolton, John; Keaver, Laura
Introduction: The deleterious effects of ageing and inactivity are compounded by the menopause which typically occurs in females aged 50+. The menopause is associated with unfavourable changes in body composition including decreased skeletal muscle mass, bone density and increased adipose tissue. This study aimed to determine the effects of a 6-week community-based intervention on nutrition knowledge and physical, metabolic, and cardiovascular health of women aged 50+ years. Methods: Nineteen participants (57 ± 6 years, 32.4 ± 7.2 kg/m 2 ) completed the intervention consisting of 2 hours of aerobic training (home-based / participant led), 2 hours of concurrent training (instructor led) and one 60-minute health workshop per week. General nutrition knowledge was assessed using an adapted validated questionnaire. Body weight, body mass index (BMI), body composition and waist circumference were measured pre and post intervention. Lower body strength endurance and cardiovascular endurance were assessed using sit-to-stand and 6-minute walk tests respectively. Point-of-care testing determined fasting glucose and lipid profile. Results: There were significant reductions in body weight (–2.2 ± 2.0 kg, p < 0.01), BMI (–0.9 ± 0.8 kg/m 2, p < 0.05), percent body fat (–1.1 ± 0.5%, p < 0.05), waist circumference (–2.4 ± 0.5 cm, p < 0.05) and fasting glucose (–0.6 ± 0.8 mmol/L) post intervention. General nutrition knowledge score (5.8 ± 0.05, p < 0.05), 6-minute walk test (Mdn = 82.5, IQR = 49.5, p < 0.05) and sit-to-stand performance increased (11.5 ± 4.5 repetitions, p < 0.05) significantly. Discussion: This intervention successfully improved body weight, BMI, body fat percent, waist circumference, fasting glucose, general nutrition knowledge, cardiovascular fitness, and lower body strength of participants. Metabolic health improved with a trend towards improved cardiovascular health.